Lightweight self-waterproof homogeneous thermal insulation wallboard and preparation method thereof

By using materials such as ultrafine silica powder, sulfoaluminate cement and reinforcing fibers in the insulation wall panels to form a honeycomb structure, the problem of inconsistent expansion and contraction of materials in traditional insulation technology is solved, and efficient thermal insulation, thermal insulation and Waterproof effect, while reducing production time and energy consumption.

CN119330678APending Publication Date: 2025-01-21JIESTONE (TIANJIN) INTEGRATED HOUSING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411778764.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The non-homogeneous materials used in traditional PC assembly insulation technology lead to inconsistent expansion and contraction of hot and cold, resulting in poor durability, local cracking, poor airtightness and waterproofing. At the same time, the production process takes a long time and energy consumption is high.

Method used

Lightweight self-waterproof homogeneous thermal insulation wall panels are used. Surface materials, cement slurries and structural materials are set in sequence, and ultrafine silica powder, sulfoaluminate cement, reinforcing fibers and light aggregates are added to form a honeycomb structure. To improve the heat preservation and insulation capabilities, and to reduce production time and energy consumption by simplifying the process and optimizing the ratio of raw materials.

Benefits of technology

It significantly improves the thermal insulation, heat insulation, waterproof and durability performance of wall panels, reduces construction time and carbon emissions, saves steaming energy, and has high economic benefits and environmental protection significance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005172229690000121
    Figure BDA0005172229690000121
  • Figure BDA0005172229690000122
    Figure BDA0005172229690000122
  • Figure BDA0005172229690000131
    Figure BDA0005172229690000131
Patent Text Reader

Abstract

The invention relates to the technical field of building refractory materials, and particularly discloses a light self-waterproof homogeneous thermal insulation wallboard and a preparation method thereof. The light self-waterproof homogeneous thermal insulation wallboard comprises a surface layer material, cement slurry and a structural material which are arranged in sequence, wherein the cement slurry comprises the following components in parts by weight: 40-45 parts of Portland cement; 10 to 15 parts of sulphoaluminate cement; 0.025 to 0.05 part of reinforcing fiber; 0.25 to 0.375 part of lightweight aggregate; 0.0375 to 0.05 part of a cement reinforcing agent; 0.05 to 0.125 part of steaming-free powder; 0.025 to 0.05 part of a water reducing agent; 0.0375 to 0.05 part of an early strength agent; and 39.225 to 49.525 parts of water. The steaming-free powder comprises superfine silicon powder with the specific surface area of 600-800m < 2 > / kg. By adjusting the raw material ratio and adding the non-steaming powder, the construction time consumption is reduced, and the steam curing energy is saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of building refractory materials, and in particular to a lightweight self-waterproof homogeneous thermal insulation wallboard and a preparation method thereof. Background Art

[0002] In buildings, the heat loss of the exterior wall enclosure structure is large, and the wall is the main component of the exterior enclosure structure. Therefore, exterior wall insulation has become a very important part of wall construction, which can not only save a lot of energy, but also provide a good living environment for residents in the building. The more commonly used insulation technology before was the traditional PC assembly insulation technology, which has certain insulation and fireproof effects, but the insulation wall used in this technology is non-uniform material with poor weather resistance and is not suitable for areas with large seasonal temperature differences. Because the thermal expansion and contraction coefficients of different materials are different, when the temperature difference between indoor and outdoor is large, it is easy to have inconsistent expansion and contraction ratios, which will lead to poor durability, local cracking, poor air tightness and poor waterproofness.

[0003] At this time, some researchers proposed that the assembled self-insulating wall technology could replace the traditional PC assembled insulation technology. Specifically, the exterior wall insulation system can be made by assembling wall materials such as concrete prefabricated parts, cement fiber reinforced product components and cement-based polystyrene particle wallboards through hoisting. The thickness and material of the wall materials can be adjusted according to different climatic conditions and building specifications to meet different insulation requirements. However, the above wall materials all use inorganic cement as the cementitious material. The production process requires cement slurry stirring, cement slurry injection between the surface material and the structural material, mold vibration molding, steam curing or autoclaving curing and natural curing. Therefore, it has the defects of long construction time and high steam curing energy consumption. Summary of the invention

[0004] In order to solve the above technical problems, the present application provides a lightweight self-waterproof homogeneous thermal insulation wall panel and a preparation method thereof.

[0005] In the first aspect, the present application provides a lightweight self-waterproof homogeneous thermal insulation wallboard, comprising a surface material, a cement slurry and a structural material arranged in sequence, wherein the cement slurry comprises the following components in parts by weight: 40-45 parts of silicate cement; 10-15 parts of sulphoaluminate cement; 0.025-0.05 parts of reinforcing fiber; 0.25-0.375 parts of lightweight aggregate; 0.0375-0.05 parts of cement reinforcing agent; 0.05-0.125 parts of steam-free powder; 0.025-0.05 parts of water reducing agent; 0.0375-0.05 parts of early strength agent; 39.225-49.525 parts of water; the steam-free powder comprises a specific surface area of ​​600-800m 2 / kg of ultrafine silicon powder.

[0006] By adopting the above technical scheme, the present application adds steam-free powder into the system, so that the oxidized substances such as tricalcium silicate, dicalcium silicate, and tetracalcium aluminoferrate in silicate cement and sulphoaluminate cement can be hydrated and hardened more quickly to form a honeycomb structure, which can greatly improve the thermal insulation and heat insulation capacity of the lightweight self-waterproof homogeneous thermal insulation wallboard; the present application also utilizes sulphoaluminate cement, which can improve the early strength of the system after adding it into the system, and ensure that the honeycomb structure has good mechanical properties during the high-speed hydration and hardening process, and it also has good density after hardening, thereby improving the waterproof capacity of the lightweight self-waterproof homogeneous thermal insulation wallboard. At the same time, the present application adds reinforcing fibers into the system, effectively improving the compressive strength and impact resistance of the lightweight self-waterproof homogeneous thermal insulation wallboard, and adding a certain amount of lightweight aggregate, which not only improves the thermal insulation and heat insulation capacity of the lightweight self-waterproof homogeneous thermal insulation wallboard, but also greatly reduces its dead weight and improves the convenience of assembly. At the same time, the raw materials in this application are cement-based modified homogeneous materials with similar hot and cold expansion and contraction coefficients. Therefore, the expansion and contraction ratios of the raw materials are roughly the same, and the possibility of local cracking, reduced air tightness and waterproofness is very low. The lightweight self-waterproof homogeneous insulation wall panels still have good durability under freeze-thaw cycles. According to experimental tests, the compressive strength of the lightweight self-waterproof homogeneous thermal insulation wall panel of the present application can reach more than 0.52MPa after 8 hours of natural curing, there is no crack on the board surface after 15 impacts, the thermal conductivity is not higher than 0.334W / (m·℃), the mass loss after 80 freeze-thaw cycles is not higher than 1.336%, and the thermal conductivity change rate is not higher than 12.41%. Therefore, it not only has good thermal insulation ability, fire resistance, waterproof performance and durability, but also has the same mechanical strength as the wall panel obtained by the traditional process (steaming for 8 hours and natural curing for 3 days), which significantly reduces the construction time and reduces the carbon emissions during the curing process. It has certain environmental protection significance, saves steaming energy, and has high economic benefits.

[0007] Specifically, the present application uses ultrafine silica powder as a steam-free powder. The ultrafine silica powder can preferentially form an ettringite mineral structure during the hydration process, generate initial hydration heat more quickly in the system, and thus increase the hydration rate of silicate cement and sulphoaluminate cement. In addition, the present application controls the specific surface area of ​​the ultrafine silica powder to be 600-800m 2 / kg, under the premise of reducing the possibility of agglomeration in the system, the steam-free effect is optimized. If the specific surface area is too large, the ultrafine silica powder cannot play an effective steam-free effect. If the specific surface area is too small, the ultrafine silica powder will have more serious agglomeration in the system, reducing the uniformity in the system and affecting the thermal insulation and heat preservation capacity of the lightweight self-waterproof homogeneous thermal insulation wallboard.

[0008] Preferably, the ultrafine silicon powder is further purified by the following method: The ultrafine silicon powder is calcined at a temperature of 600-800° C. for 4-4.5 hours and then cooled to room temperature to obtain purified ultrafine silicon powder.

[0009] By adopting the above technical solution, the present application places the ultrafine silicon powder at a certain temperature for calcination treatment, effectively removing the free carbon in the ultrafine silicon powder, with a removal rate of more than 66%, and having almost no effect on the specific surface area of ​​the ultrafine silicon powder. Since the free carbon is mostly attached to the surface of the ultrafine silicon powder, the effective contact area between the purified ultrafine silicon powder and water is larger, which can further accelerate the speed of generating initial hydration heat in the system, thereby increasing the hydration and hardening speed of the oxidized substances in the system, and further improving the compressive strength and impact resistance of the lightweight self-waterproof homogeneous thermal insulation wallboard under the premise of unchanged natural curing time.

[0010] Purified ultrafine silica powder can reduce the viscosity of the system and improve fluidity. Its surface morphology is smoother during vibration molding on the mold platform. At the same time, the purified ultrafine silica powder can be more fully combined with other hydration products after hydration, thereby reducing the porosity of the system. Coupled with the smoother surface morphology, the durability and waterproof ability of the lightweight self-waterproof homogeneous thermal insulation wall panel of the present application are further improved.

[0011] Preferably, the reinforcing fibers include polypropylene chopped fibers and natural straw fibers in a weight ratio of 1:(0.5-1).

[0012] By adopting the above technical scheme, the present application utilizes the combination of polypropylene short fibers and natural straw fibers, wherein the polypropylene short fibers can play the advantages of low dead weight, high strength and good dispersibility in the system, and the natural straw fibers have good high temperature resistance, which can inhibit the volume shrinkage and crack expansion of the materials in the system under temperature difference changes. After the two are mixed in a certain proportion, they can give full play to the synergistic effect and optimize the system performance. Compared with other fibers with reinforcing effects (such as steel fibers and alkali-free glass fibers), polypropylene short fibers and natural straw fibers have lower dead weight and higher dispersibility, and can effectively improve the impact resistance and durability of lightweight self-waterproof homogeneous thermal insulation wall panels without affecting the bulk density and uniformity of the system. They also have higher flexibility, which can effectively improve the bending bearing capacity of lightweight self-waterproof homogeneous thermal insulation wall panels in assembly applications.

[0013] Preferably, the natural wheat straw fiber is further subjected to alkali treatment by the following method: The natural wheat straw fiber is immersed in 8-10wt% sodium hydroxide aqueous solution for 20-60 minutes, then taken out and immersed in water again for 2-3 minutes, taken out and dried to obtain the alkali-treated natural wheat straw fiber.

[0014] By adopting the above technical scheme, the present application subjected natural straw fibers to an alkaline solution immersion treatment, thereby obtaining fibrillated alkali-treated natural straw fibers, which had a larger effective contact area and higher interface compatibility with the cement matrix, and the effect of inhibiting volume shrinkage and crack expansion was further optimized.

[0015] Preferably, the lightweight aggregate comprises expanded perlite, polystyrene particles and inorganic vitrified microspheres in a weight ratio of 2:(0.2-0.3):(0.1-0.15).

[0016] By adopting the above technical scheme, the lightweight aggregate of the present application utilizes expanded perlite, polystyrene particles and inorganic vitrified microspheres with low thermal conductivity, which are mixed in a certain weight ratio. Under the condition of ensuring that the lightweight aggregate has good thermal insulation and heat preservation capabilities, the bulk density of the lightweight aggregate is reduced as much as possible, and the convenience of assembling lightweight self-waterproof homogeneous thermal insulation wall panels is improved. Among them, compared with the other two thermal insulation materials, the expanded perlite has the most moderate thermal conductivity and bulk density, which can well balance the weight and thermal insulation capabilities of the lightweight aggregate. The polystyrene particles have extremely low bulk density and good hydrophobicity, which can improve the waterproof ability of the lightweight aggregate. The inorganic vitrified microspheres have a smaller particle size (not more than 80um) and can be embedded. The inorganic vitrified microspheres are introduced into the voids produced after mixing with other components in the system, thereby reducing the overall porosity, optimizing the air tightness of the lightweight self-waterproof homogeneous thermal insulation wallboard, and improving the waterproof ability; and the present application strictly controls the weight ratio of the three. If the amount of inorganic vitrified microspheres added is too large, due to their large bulk density, the lightweight characteristics of the lightweight self-waterproof homogeneous thermal insulation wallboard will be affected; if the amount of polystyrene particles added is too large, the compressive strength of the lightweight aggregate will be reduced; if the amount of expanded perlite added is too large, due to its good water absorption, it will slow down the hardening speed in the system, reduce the compressive strength and impact resistance of the lightweight self-waterproof homogeneous thermal insulation wallboard after 8 hours of natural curing, and affect the waterproof ability.

[0017] Preferably, the water reducer is a lignin water reducer.

[0018] By adopting the above technical scheme, the lignin water reducer of the present application can effectively improve the compressive strength and impact resistance of lightweight self-waterproof homogeneous insulation wall panels, and compared with other water reducers (polycarboxylic acid water reducers and naphthalene water reducers), it has a relatively weaker retarding ability, and can avoid excessively slowing down the hardening rate in the system while achieving an effective reinforcement effect.

[0019] Preferably, the raw materials used also include 0.05-0.075 parts by weight of acrylic emulsion.

[0020] By adopting the above technical scheme, the present application also adds a certain amount of acrylic emulsion into the system, thereby improving the bonding degree between the raw materials in the system, and at the same time improving the waterproof ability of the lightweight self-waterproof homogeneous thermal insulation wall panel, and also making it have good self-adhesive ability. In actual use, it can be tightly bonded to the surface materials (calcium silicate board, metal panel) or steel structure components that need to be insulated and heat-insulated, and can be shaped without other post-processing steps, which greatly improves its practicality and installation convenience. Compared with other emulsions with bonding ability (silicone acrylic emulsion and styrene acrylic emulsion), acrylic emulsion has a lower minimum film-forming temperature, and also has a wider temperature application range, thereby expanding the application range of lightweight self-waterproof homogeneous thermal insulation wall panels, and can maintain good self-adhesive properties under different climatic conditions.

[0021] At the same time, experimental data have shown that when acrylic emulsion is blended with natural straw fiber in the system, acrylic emulsion can reduce the hydrophilicity of natural straw fiber and the silica content on its surface, thereby improving the bonding performance between natural straw fiber and cement matrix, thereby further optimizing the effect of natural straw fiber in inhibiting volume shrinkage and crack expansion.

[0022] In a second aspect, the present application provides a method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard, comprising the following steps: S1. Mixing: Mix a water reducing agent, an early strength agent, a cement reinforcing agent and water and stir them evenly to obtain a preparatory liquid, then add silicate cement, sulphoaluminate cement and reinforcing fiber into the preparatory liquid, stir evenly, then add lightweight aggregate, stir evenly, finally add steam-free powder, stir all the raw materials evenly to obtain cement slurry; S2, mold table vibration molding; S3. Natural curing: After standing at a temperature of 20-22°C for 2.8-3 hours, demould to obtain the board to be cured, place it in a dark and ventilated place for curing for 7.8-8 hours to obtain a lightweight self-waterproof homogeneous thermal insulation wallboard.

[0023] By adopting the above technical scheme, the present application first mixes a water reducer, an early strength agent, a cement reinforcing agent and water to obtain a preparatory liquid, then adds solid substances (Silicate cement, sulphoaluminate cement and reinforcing fiber) into the preparatory liquid, and finally adds the steam-free powder that can quickly increase the hydration speed, and pours it into a mold after stirring evenly, vibrates it into shape, smoothes the upper surface until there is obvious cement slurry, then turns off the vibration of the mold, demolds, and naturally cures, and a lightweight self-waterproof homogeneous thermal insulation wall panel can be obtained within 8 hours; the method has a simple and reliable production process, a wide source of raw materials, low cost, can realize automatic continuous intelligent production, low production energy consumption and carbon emissions, and has high economic benefits and wide use value.

[0024] Preferably, in step S1, silicate cement, sulphoaluminate cement and reinforcing fiber are first mixed evenly and then blended with the preparatory liquid.

[0025] By adopting the above technical scheme, the present application first pre-uniformly blends the solid substances (Silicate cement, sulfoaluminate cement and reinforcing fibers) and then mixes them with the preparatory liquid, which can greatly weaken the agglomeration phenomenon of the solid substances in the liquid, significantly improve the dispersion uniformity of the raw materials in the system, and have good density after hardening, thereby improving the air tightness of the lightweight self-waterproof homogeneous thermal insulation wall panels, and further improving the thermal insulation and heat insulation capabilities.

[0026] Preferably, in step S1, acrylic emulsion is added and mixed with a water reducing agent, an early strength agent, a cement reinforcing agent and water to obtain a preparatory solution.

[0027] In summary, this application has the following beneficial technical effects: 1. The compressive strength of the lightweight self-waterproof homogeneous thermal insulation wallboard of the present application can reach more than 2.2MPa after 8 hours of natural curing, and there is no crack on the board surface after 5 impacts. It has the same mechanical strength as the wallboard obtained by the traditional process (steaming for 8 hours and natural curing for 3 days). The 3-day compressive strength can reach the compressive strength value of the standard curing for 28 days, which is not less than 3.5MPa. At the same time, the thermal conductivity is not higher than 0.068W / (m·℃), the mass loss after 80 freeze-thaw cycles is not higher than 1.336%, and the thermal conductivity change rate is not higher than 12.41%. On the premise of having good thermal insulation ability and mechanical strength, it significantly reduces the construction time and reduces the carbon emissions during the curing process, which has certain environmental protection significance, and also saves steaming energy, with high economic benefits; 2. The preparation method of the lightweight self-waterproof homogeneous thermal insulation wallboard of the present application has a simple and reliable production process, a wide range of raw material sources, low cost, can realize automatic continuous intelligent production, low production energy consumption and carbon emissions, and has high economic benefits and wide use value. DETAILED DESCRIPTION

[0028] Material Source Unless otherwise specified, the raw materials used in this application are all commercially available products, specifically: Ultrafine silicon powder was purchased from Shanghai Yurui New Material Technology Co., Ltd., with a specific surface area of ​​600m 2 / kg、800m 2 / kg、500m 2 / kg and 900m 2 / kg; Polycarboxylic acid water reducer was purchased from Beijing Jinyu Cement Energy Saving Technology Co., Ltd., model JY-TS-1; Calcium formate was purchased from Jinan Sunny Chemical Technology Co., Ltd. with a fineness of 100 mesh; Triethanolamine was purchased from Jinan Juxing Chemical Co., Ltd., with an effective content of not less than 99%; Alumina was purchased from Wujiang Yongsheng Chemical Co., Ltd.; Portland cement was purchased from Tianjin Jinyu Zhenxing Environmental Protection Technology Co., Ltd., model P.O42.5, with a specific surface area of ​​390±30m 2 / kg, density is 2300kg / m 3 ; Sulphoaluminate cement was purchased from Tianjin Jinyu Zhenxing Environmental Protection Technology Co., Ltd., model P.O42.5, with a specific surface area of ​​380±20m 2 / kg, density is 2800kg / m 3 ; Natural wheat straw fiber was provided by Lingshou County Xinde Agricultural Products Co., Ltd., and the diameter of the wheat straw was cut into a length of 2-3 cm, and the melting temperature was 900±150℃; Polypropylene chopped fibers were purchased from Shandong Futai Fiber Co., Ltd., with a fiber diameter of 25 ± 5 μm, a fiber length of 6 mm, an elastic modulus of 42 GPa, and a tensile strength of 1600 MPa; Steel fibers were purchased from Shandong Yiheng Engineering Materials Co., Ltd. with a fiber diameter of 0.7 ± 0.2 mm, a fiber length of 6 mm, an elastic modulus of 200 GPa, and a tensile strength of 1000 MPa; The alkali-free glass fiber was purchased from Taian Haoda New Materials Co., Ltd., with a fiber diameter of 10 ± 1 μm, a fiber length of 6 mm, an elastic modulus of 80 GPa, and a tensile strength of 1800 MPa; Expanded perlite was purchased from Houpu Mining Materials Factory, Xinyang City, Henan Province, with a particle size of 3 ± 1 mm and a thermal conductivity of 0.035 W / (m·℃); The particle size of polystyrene particles is 7±1mm, the thermal conductivity is 0.045W / (m·℃), and the bulk density is 15±2kg; Inorganic vitrified microspheres were purchased from Qingdong Glass Microspheres Factory, Dongguan City, Guangdong Province, with a bulk density of 150 kg, a particle size of 75 ± 5 μm, a surface vitrified closed porosity of 95%, a thermal conductivity of 0.032-0.045 W / (m·℃), and a Mohs hardness of 6.5 ± 0.5; Lignin water reducer was purchased from Hubei Xingdongcheng Chemical Co., Ltd., and the active ingredient is C 20 H 24 CaO 10 S2, water reduction rate is not less than 10%; Naphthalene-based water reducer was purchased from Jinan Shanhai Chemical Technology Co., Ltd., product specification is FDN-C; Styrene acrylic emulsion was purchased from Beijing Mengtai Weiye Building Materials Co., Ltd., model MT-1102, solid content 50%, minimum film-forming temperature 22°C; The silicone-acrylic emulsion was purchased from Beijing Mengtai Weiye Building Materials Co., Ltd., model MT-8000, solid content 50%, minimum film-forming temperature 20°C; The acrylic emulsion was purchased from Rohm and Haas Company of the United States, model MAC-261P, solid content 50%, and minimum film-forming temperature 18°C.

[0029] The present application is further described in detail below in combination with preparation examples, embodiments and comparative examples.

[0030] Preparation Example 1 The preparation method of purified ultrafine silicon powder adopts the following steps: 150g of specific surface area is 600m 2 / kg ultrafine silicon powder is calcined at 600°C for 4.5h and cooled to room temperature to obtain purified ultrafine silicon powder.

[0031] Preparation Example 2 The preparation method of purified ultrafine silicon powder adopts the following steps: 150g of specific surface area is 600m 2 / kg ultrafine silicon powder is calcined at 800°C for 4 hours and cooled to room temperature to obtain purified ultrafine silicon powder.

[0032] Preparation Example 3 The preparation method of alkali-treated natural wheat straw fiber adopts the following steps: 30 g of natural wheat straw fiber was immersed in 500 mL of 10 wt % sodium hydroxide aqueous solution for 60 min, then the natural wheat straw fiber was taken out and immersed in water again for 3 min, then taken out and dried to constant weight to obtain alkali-treated natural wheat straw fiber.

[0033] Preparation Example 4 The preparation method of alkali-treated natural wheat straw fiber adopts the following steps: 30 g of natural wheat straw fiber was immersed in 500 mL of 8 wt % sodium hydroxide aqueous solution for 20 min, then the natural wheat straw fiber was taken out and immersed in water again for 2 min, then taken out and dried to constant weight to obtain alkali-treated natural wheat straw fiber.

[0034] Example 1.1 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard comprises the following steps: S1. Mixing: Mix 25g of water reducer (polycarboxylic acid water reducer), 50g of early strength agent (25g of calcium formate, 25g of triethanolamine), 37.5g of cement reinforcing agent (alumina) and 49.525kg of water and stir evenly to obtain a preparatory solution. Then, add 40kg of silicate cement, 15kg of sulphoaluminate cement and 25g of reinforcing fiber (steel fiber) to the preparatory solution, stir evenly, then add 375g of lightweight aggregate (expanded perlite), stir evenly, and finally add 50g of steam-free powder (specific surface area of ​​600m 2 / kg of ultrafine silicon powder), and all the raw materials are stirred evenly to obtain cement slurry; S2, mold platform vibration molding: fix the calcium silicate board and the steel frame structure components on both sides of the mold platform through a vertical mold platform, fill the cement slurry obtained in step S1 between the two calcium silicate boards, and then turn on the high-frequency mold platform vibration for 1 minute, and smooth the upper surface of the wall panel until there is obvious cement slurry on the upper surface of the wall panel, and then turn off the mold platform vibration; S3. Natural curing: After standing at a temperature of 22°C for 2.8 hours, demould to obtain the board to be cured, place it in a dark and ventilated place for curing for 8 hours to obtain a lightweight self-waterproof homogeneous thermal insulation wallboard.

[0035] Example 1.2 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard comprises the following steps: S1. Mixing: Mix 50g of water reducer (polycarboxylic acid water reducer), 37.5g of early strength agent (17.5g of calcium formate, 20g of triethanolamine), 50g of cement reinforcing agent (alumina) and 39.225kg of water and stir evenly to obtain a preparatory liquid. Then, add 45kg of silicate cement, 10kg of sulphoaluminate cement and 50g of reinforcing fiber (steel fiber) to the preparatory liquid, stir evenly, then add 250g of lightweight aggregate (expanded perlite), stir evenly, and finally add 125g of steam-free powder (specific surface area of ​​800m 2 / kg of ultrafine silicon powder), and all the raw materials are stirred evenly to obtain cement slurry; S2, mold platform vibration molding: fix the aluminum single plate and the steel frame structure components on both sides of the mold platform through the vertical mold platform, fill the cement slurry obtained in step S1 between the two calcium silicate boards, and then turn on the high-frequency mold platform vibration for 1 minute, and smooth the upper surface of the wall panel until there is obvious cement slurry on the upper surface of the wall panel, and then turn off the mold platform vibration; S3. Natural curing: After standing at a temperature of 20°C for 3 hours, demould to obtain the board to be cured, place it in a dark and ventilated place for curing for 7.8 hours to obtain a lightweight self-waterproof homogeneous thermal insulation wallboard.

[0036] Example 2.1 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard, which is different from Example 1.1 in that 50g of ultrafine silicon powder in step S1 is replaced by 50g of purified ultrafine silicon powder obtained in Preparation Example 1, and the rest is the same as Example 1.1.

[0037] Example 2.2 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard, which is different from Example 1.1 in that 50g of ultrafine silicon powder in step S1 is replaced by 50g of purified ultrafine silicon powder obtained in Preparation Example 2, and the rest is the same as Example 1.1.

[0038] Example 3.1 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard, which is different from Example 1.1 in that: 25g of steel fiber in step S1 is replaced by 25g of polypropylene chopped fiber, and the rest is the same as Example 1.1.

[0039] Example 3.2 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wall panel, which is different from Example 1.1 in that: 25g of steel fiber in step S1 is replaced by 25g of natural straw fiber, and the rest is the same as Example 1.1.

[0040] Example 3.3 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wall panel, which is different from Example 1.1 in that 25g of steel fiber in step S1 is replaced by 25g of alkali-free glass fiber, and the rest is the same as Example 1.1.

[0041] Example 3.4 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wall panel, which is different from Example 1.1 in that: 25g of steel fiber in step S1 is replaced by 12.5g of polypropylene chopped fiber and 12.5g of natural straw fiber, and the rest is the same as Example 1.1.

[0042] Example 3.5 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wall panel, which is different from Example 1.1 in that: 25g of steel fiber in step S1 is replaced by 15g of polypropylene chopped fiber and 10g of natural straw fiber, and the rest is the same as Example 1.1.

[0043] Example 3.6 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wall panel, which is different from Example 1.1 in that: 25g of steel fiber in step S1 is replaced by 12.5g of steel fiber and 12.5g of natural straw fiber, and the rest is the same as Example 1.1.

[0044] Example 3.7 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wall panel, which is different from Example 1.1 in that: 25g of steel fiber in step S1 is replaced by 12.5g of polypropylene chopped fiber and 12.5g of alkali-free glass fiber, and the rest is the same as Example 1.1.

[0045] Example 4.1 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wall panel, which differs from Example 3.4 in that: 12.5g of natural straw fiber in step S1 is replaced by 12.5g of alkali-treated natural straw fiber obtained in Preparation Example 3, and the rest is the same as Example 3.4.

[0046] Example 4.2 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wall panel, which differs from Example 3.4 in that: 12.5g of natural straw fiber in step S1 is replaced by 12.5g of alkali-treated natural straw fiber obtained in Preparation Example 4, and the rest is the same as Example 3.4.

[0047] Example 5.1 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard, which is different from Example 1.1 in that 375g of expanded perlite in step S1 is replaced with 375g of polystyrene particles, and the rest is the same as Example 1.1.

[0048] Example 5.2 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard, which is different from Example 1.1 in that 375g of expanded perlite in step S1 is replaced with 375g of inorganic vitrified microspheres, and the rest is the same as Example 1.1.

[0049] Example 5.3 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard, which is different from Example 1.1 in that 375g of expanded perlite in step S1 is replaced with 326g of expanded perlite and 49g of polystyrene particles, and the rest is the same as Example 1.1.

[0050] Example 5.4 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard, which is different from Example 1.1 in that 375g of expanded perlite in step S1 is replaced with 357g of expanded perlite and 18g of inorganic vitrified microspheres, and the rest is the same as Example 1.1.

[0051] Example 5.5 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard, which is different from Example 1.1 in that 375g of expanded perlite in step S1 is replaced with 281.25g of polystyrene particles and 93.75g of inorganic glass microspheres, and the rest is the same as Example 1.1.

[0052] Example 5.6 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard, which is different from Example 1.1 in that: 375g of expanded perlite in step S1 is replaced with 312.5g of expanded perlite, 46.875g of polystyrene particles and 15.625g of inorganic glass microspheres, and the rest is the same as Example 1.1.

[0053] Example 5.7 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard, which is different from Example 1.1 in that 375g of expanded perlite in step S1 is replaced with 319.1g of expanded perlite, 31.9g of polystyrene particles and 24g of inorganic glass microspheres, and the rest is the same as Example 1.1.

[0054] Example 6.1 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard, which is different from Example 1.1 in that: the polycarboxylic acid water reducer in step S1 is completely replaced by a naphthalene water reducer, and the rest is the same as Example 1.1.

[0055] Example 6.2 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard, which is different from Example 1.1 in that: the polycarboxylic acid water reducer in step S1 is completely replaced by a lignin water reducer, and the rest is the same as Example 1.1.

[0056] Example 7.1 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard is different from that of Example 1.1 in that: in step S1, 50g of acrylic emulsion is further added to blend with the preparatory liquid, and the rest is the same as that of Example 1.1.

[0057] Example 7.2 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard is different from that of Example 1.1 in that: in step S1, 75g of acrylic emulsion is further added to blend with the preparatory liquid, and the rest is the same as that of Example 1.1.

[0058] Example 7.3 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard is different from that of Example 1.1 in that: in step S1, 50g of silicone acrylic emulsion is also added to blend with the preparatory liquid, and the rest is the same as that of Example 1.1.

[0059] Example 7.4 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard is different from that of Example 1.1 in that: in step S1, 50g of styrene acrylic emulsion is also added to blend with the preparatory liquid, and the rest is the same as that of Example 1.1.

[0060] Example 7.5 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard is different from that of Example 2.1 in that: in step S1, 50g of acrylic emulsion is also added to blend with the preparatory liquid, and the rest is the same as that of Example 2.1.

[0061] Example 7.6 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard is different from that of Example 3.4 in that: in step S1, 50g of acrylic emulsion is also added to blend with the preparatory liquid, and the rest is the same as that of Example 3.4.

[0062] Example 7.7 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard is different from that of Example 4.1 in that: in step S1, 50g of acrylic emulsion is also added to blend with the preparatory liquid, and the rest is the same as that of Example 4.1.

[0063] Example 7.8 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard, which is different from Example 5.7 in that: in step S1, 50g of acrylic emulsion is also added to blend with the preparatory liquid, and the rest is the same as Example 5.7.

[0064] Example 7.9 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard is different from that of Example 6.2 in that: in step S1, 50g of acrylic emulsion is also added to blend with the preparatory liquid, and the rest is the same as that of Example 6.2.

[0065] Example 8 A method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard, which is different from Example 1.1 in that: in step S1, silicate cement, sulphoaluminate cement and reinforcing fiber are first mixed evenly and then blended with the preparatory liquid, and the rest is the same as Example 1.1.

[0066] Comparative Example 1 The difference from Example 1.1 is that the steam-free powder in step S1 is removed, the curing for 8 hours in step S3 is replaced by steam curing for 8 hours, and natural curing is continued for 3 days. The rest is the same as Example 1.1.

[0067] Comparative Example 2.1 The difference from Example 1.1 is that the steam-free flour in step S1 is removed, and the rest is the same as Example 1.1.

[0068] Comparative Example 2.2 The difference from Example 1.1 is that the sulphoaluminate cement in step S1 is completely replaced by silicate cement, and the rest is the same as Example 1.1.

[0069] Comparative Example 2.3 The difference from Example 1.1 is that the lightweight aggregate in step S1 is removed, and the rest is the same as Example 1.1.

[0070] Comparative Example 2.4 The difference from Example 1.1 is that the reinforcing fiber in step S1 is removed, and the rest is the same as Example 1.1.

[0071] Comparative Example 3.1 The difference from Example 1.1 is that the specific surface area of ​​600m 2 / kg of ultrafine silicon powder is completely replaced with a specific surface area of ​​500m 2 / kg of ultrafine silicon powder, and the rest are the same as in Example 1.1.

[0072] Comparative Example 3.2 The difference from Example 1.1 is that the specific surface area of ​​600m 2 / kg of ultrafine silicon powder was completely replaced with a specific surface area of ​​900m 2 / kg of ultrafine silicon powder, and the rest are the same as in Example 1.1.

[0073] Performance Testing The lightweight self-waterproof homogeneous insulation wall panels obtained in Examples 1.1-8 of the present application and Comparative Examples 1-3.2 were tested (sample size 2440 mm × 610 mm × 100 mm), wherein: the test basis is the inspection items specified in GB / T 23451-2023 "Lightweight partition wall panels for construction", including: hanging force, moisture content, drying shrinkage, fire resistance / combustion performance, compressive strength (8h and 3d), impact resistance, surface density, bending load, softening coefficient, air sound insulation and self-adhesion ability; the thermal conductivity is tested according to the record in GB / T 10294-2008 "Determination of steady-state thermal resistance and related properties of insulation materials - Protective hot plate method"; freeze-thaw cycle test, specifically: freezing at -19±4°C for 8h, thawing at 18±4°C for 4h, a total of 12h, which is 1 freeze-thaw cycle, and the number of cycles is 80 times. During the test, ensure that the freezing temperature of the center of the wall panel is greater than -10°C, and the time taken to heat from the lowest temperature to the highest temperature is no more than 1.5h. Test the thermal conductivity change rate and mass loss, and record all the data in Tables 1-3 (Note: the hanging force, moisture content, drying shrinkage value and fire resistance / combustion performance of Examples 2.1-8 are basically the same as those of Example 1.1, and the moisture content and drying shrinkage value of Comparative Example 1-3.2 are basically the same as those of Example 1.1. In order to clearly compare the differences between the examples, no detailed record is made here).

[0074] Table 1 Table 2 Table 2 Table 3 Data Analysis: As can be seen from Table 1-3, the thermal conductivity of Examples 1.1-1.2 is 0.065-0.068 W / (m·℃), the 8h compressive strength is 2.2-2.3 MPa, the 3d compressive strength is 3.8-4.0 MPa, the impact resistance can reach more than 5 times, the mass loss after 80 freeze-thaw cycles is not higher than 1.336%, the thermal conductivity change rate is not higher than 12.39%, and the surface density is 84.4-86.0 kg / m 2 , the bending bearing capacity can reach 2.75-3.05N, the softening coefficient can reach 0.89-0.92, the fire resistance / combustion grade can reach A2 level, and the air sound insulation volume can reach 40-42, which proves that the application adopts the steam-free powder to make the oxidized substances such as tricalcium silicate, dicalcium silicate, and tetracalcium aluminoferrate in silicate cement and sulphoaluminate cement hydrate and harden more quickly and form a honeycomb structure, and sulphoaluminate cement, lightweight aggregate and other raw materials are added. The various substances cooperate with each other and give full play to the synergistic effect. Therefore, the lightweight self-waterproof homogeneous insulation wall panel of the present application not only has good thermal insulation capacity, fire resistance, waterproof performance and durability, but also has the same mechanical strength as the wall panel obtained under the traditional process (steaming for 8 hours and natural curing for 3 days), which significantly reduces the construction time and reduces the carbon emissions during the curing process. It has certain environmental protection significance, saves steaming energy, and has high economic benefits; As can be seen from Table 2, the 8h compressive strength, 3d compressive strength, impact resistance, mass loss after 80 freeze-thaw cycles, thermal conductivity change rate after 80 freeze-thaw cycles, and softening coefficient of Examples 2.1-2.2 are all better than those of Example 1.1, proving that the present application purifies the ultrafine silicon powder to obtain purified ultrafine silicon powder with a low free carbon content, which can reduce the viscosity of the system, improve the fluidity, improve the surface smoothness of the wallboard, and reduce the porosity of the system, thereby improving the durability and waterproofness of the lightweight self-waterproof homogeneous thermal insulation wallboard, and at the same time accelerate the speed of initial hydration heat generated in the system, thereby improving the hydration and hardening speed of the oxidized substances in the system, and further improve the mechanical properties of the lightweight self-waterproof homogeneous thermal insulation wallboard under the premise of unchanged natural curing time; In Examples 3.1-3.7, the difference from Example 1.1 is that different types of reinforcing fibers are replaced and the amount of reinforcing fibers is adjusted. The results show that the surface density, impact resistance, mass loss after 80 freeze-thaw cycles, thermal conductivity change rate after 80 freeze-thaw cycles, and bending load of Examples 3.4-3.5 are in the optimal balance, proving that the present application uses a certain amount of polypropylene chopped fibers and natural straw fibers to mix, which can give full play to the synergistic effect and optimize the system performance. Compared with the steel fibers in Example 1.1 and the alkali-free glass fibers in Example 3.3, the polypropylene chopped fibers have a better performance than the steel fibers in Example 1.1 and the alkali-free glass fibers in Example 3.3. The fiber and natural wheat straw fiber have lower deadweight and higher dispersion ability. The polypropylene short-cut fiber can play the advantages of low deadweight, high strength and good dispersion in the system. The natural wheat straw fiber has good high temperature resistance and can inhibit the volume shrinkage and crack expansion of the materials in the system under temperature difference changes. The reinforcing fiber of the present application can effectively improve the impact resistance and durability of the lightweight self-waterproof homogeneous thermal insulation wallboard without affecting the bulk density and uniformity of the system. It also has higher flexibility and can effectively improve the bending bearing of the lightweight self-waterproof homogeneous thermal insulation wallboard in assembly applications. The 8h compressive strength, 3d compressive strength, impact resistance and flexural bearing capacity of Examples 4.1-4.2 are all better than those of Example 3.4, proving that the present application has subjected the natural straw fiber to an alkali solution immersion treatment, obtained fibrillated alkali-treated natural straw fiber, and replaced the untreated natural straw fiber, thereby increasing the effective contact area and interface compatibility between the natural straw fiber and the cement matrix, and further optimizing the effect of inhibiting volume shrinkage and crack expansion, thereby further improving the compressive strength, impact resistance and flexural bearing capacity of the lightweight self-waterproof homogeneous thermal insulation wallboard; In Examples 5.1-5.7, the difference from Example 1.1 is that different types of lightweight aggregates are replaced and the amount of lightweight aggregates is adjusted. The experimental results show that the thermal conductivity, surface density, 8h compressive strength, 3d compressive strength, impact resistance and softening coefficient of Examples 5.6-5.7 are in the optimal balance, proving that the present application uses expanded perlite, polystyrene particles and inorganic vitrified microspheres with low thermal conductivity to mix and use in a certain weight ratio, while ensuring that the lightweight aggregate has good thermal insulation and heat preservation capabilities, and reduces the bulk density of the lightweight aggregate as much as possible, thereby improving the convenience of assembling the lightweight self-waterproof homogeneous thermal insulation wallboard, reducing the overall porosity, optimizing the air tightness of the lightweight self-waterproof homogeneous thermal insulation wallboard, and improving the waterproof ability; The 8h compressive strength, 3d compressive strength and impact resistance of Example 6.1 are basically the same as those of Example 1.1, and the 8h compressive strength, 3d compressive strength and impact resistance of Example 6.2 are all higher than those of Example 1.1, which proves that the lignin water reducer selected in this application can effectively improve the compressive strength and impact resistance of the lightweight self-waterproof homogeneous insulation wallboard, and has a relatively weak retarding ability compared to the polycarboxylic acid water reducer in Example 1.1 and the naphthalene water reducer in Example 6.1, and can avoid excessively slowing down the hardening speed in the system while achieving an effective reinforcement effect; Compared with Example 1.1, Examples 7.1-7.2 have self-adhesive properties and a certain improvement in softening coefficient, which proves that the application improves the bonding degree between the raw materials in the system by adding a certain amount of acrylic emulsion into the system, and at the same time improves the waterproof ability of the lightweight self-waterproof homogeneous insulation wallboard, and also has good self-adhesive ability. In actual use, it can be tightly bonded to the surface material (calcium silicon board, metal panel) or steel structure components that need to be insulated and heat-insulated, and can be shaped without other post-processing steps, which greatly improves its practicality and installation convenience; The mass loss and thermal conductivity change rate of Examples 7.3-7.4 after 80 freeze-thaw cycles are lower than those of Example 7.1, which proves that the acrylic emulsion of the present application has a lower minimum film-forming temperature than the silicone acrylic emulsion in Example 7.3 and the styrene acrylic emulsion in Example 7.4, and thus has a wider temperature application range, thereby expanding the application range of lightweight self-waterproof homogeneous thermal insulation wallboards, and can maintain good self-adhesive properties under different climatic conditions; Examples 7.5-7.9 added acrylic emulsion on the basis of Examples 2.1, 3.4, 4.1, 5.7 and 6.2, respectively. The results showed that acrylic emulsion can indeed effectively improve the waterproof ability and self-adhesive performance. At the same time, compared with Example 3.4, the improvement rates of 8h compressive strength, 3d compressive strength, impact resistance and bending bearing of Example 7.6 are higher, which proves that acrylic emulsion can reduce the hydrophilicity of natural straw fiber and the silica content on its surface, so as to improve the bonding performance between natural straw fiber and cement matrix, thereby further optimizing the effect of natural straw fiber in inhibiting volume shrinkage and crack expansion; The thermal conductivity of Example 8 is much lower than that of Example 1.1, while the softening coefficient and airborne sound insulation are much higher than those of Example 1.1, which proves that the solid substances are pre-mixed uniformly before being mixed with the preparatory liquid, which can greatly weaken the agglomeration of the solid substances in the liquid, significantly improve the dispersion uniformity of the raw materials in the system, and have good compactness in the system after hardening, thereby improving the air tightness of the lightweight self-waterproof homogeneous thermal insulation wallboard, and further improving the thermal insulation capacity and heat insulation capacity; The 8h compressive strength, impact resistance and bending load of Comparative Example 1 are similar to those of Example 1.1, while the 3d compressive strength is much lower than that of Example 1.1. At the same time, the thermal conductivity, 8h compressive strength, 3d compressive strength, impact resistance and bending load of Comparative Example 2.1 are much weaker than those of Example 1.1, and the hanging force is lower than 1000N, and the fire resistance / combustion performance is also poor. The 8h compressive strength, 3d compressive strength, impact resistance and bending load of Comparative Example 2.2 are much weaker than those of Example 1.1. The thermal conductivity of Comparative Example 2.3 is much weaker than that of Example 1.1, the waterproof ability is general, and the fire resistance / combustion performance is also poor. The 8h compressive strength, 3d compressive strength, impact resistance and bending load of Comparative Example 2.4 are much weaker than Example 1.1 proves that the present application uses steam-free powder to make the oxidized substances such as tricalcium silicate, dicalcium silicate, and tetracalcium aluminoferrate in silicate cement and sulphoaluminate cement hydrate, harden and form a honeycomb structure more quickly, and sulphoaluminate cement, lightweight aggregate and other raw materials are added. The various substances cooperate with each other to give full play to the synergistic effect. Therefore, the lightweight self-waterproof homogeneous thermal insulation wall panel of the present application not only has good thermal insulation ability, fire resistance, waterproof performance and durability, but also has the same mechanical strength as the wall panel obtained by traditional process (steaming for 8 hours and natural curing for 3 days), which significantly reduces the construction time and reduces the carbon emissions during the curing process. It has certain environmental protection significance, saves steaming energy, and has very high economic benefits.

[0075] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A lightweight self-waterproof homogeneous thermal insulation wallboard, comprising a surface material, cement slurry and structural material arranged in sequence, characterized in that: The cement slurry comprises the following components in parts by weight: 40-45 parts of Portland cement; 10-15 parts of sulphoaluminate cement; 0.025-0.05 parts of reinforcing fiber; 0.25-0.375 parts of lightweight aggregate; 0.0375-0.05 parts of cement reinforcing agent; 0.05-0.125 parts of steam-free powder; 0.025-0.05 parts of water reducing agent; 0.0375-0.05 parts of early strength agent; 39.225-49.525 parts of water; the steam-free powder includes a specific surface area of ​​600-800m 2 / kg of ultrafine silicon powder.

2. A lightweight self-waterproof homogeneous thermal insulation wallboard according to claim 1, characterized in that: The ultrafine silicon powder is also purified by the following method: The ultrafine silicon powder is calcined at a temperature of 600-800° C. for 4-4.5 hours and then cooled to room temperature to obtain purified ultrafine silicon powder.

3. A lightweight self-waterproof homogeneous thermal insulation wallboard according to claim 1, characterized in that: The reinforcing fibers include polypropylene short-cut fibers and natural straw fibers in a weight ratio of 1:(0.5-1).

4. A lightweight self-waterproof homogeneous thermal insulation wallboard according to claim 3, characterized in that: The natural straw fiber is also alkali treated by the following method: The natural wheat straw fiber is immersed in an 8-10wt% sodium hydroxide aqueous solution for 20-60 minutes, then taken out and immersed in water again for 2-3 minutes, taken out and dried to obtain the alkali-treated natural wheat straw fiber.

5. The lightweight self-waterproof homogeneous thermal insulation wallboard according to claim 1, characterized in that: The lightweight aggregate comprises expanded pearlite, polystyrene particles and inorganic vitrified microspheres in a weight ratio of 2:(0.2-0.3):(0.1-0.15).

6. A lightweight self-waterproof homogeneous thermal insulation wallboard according to claim 1, characterized in that: The water reducing agent is a lignin water reducing agent.

7. A lightweight self-waterproof homogeneous thermal insulation wallboard according to any one of claims 1 to 6, characterized in that: The raw materials used also include 0.05-0.075 parts by weight of acrylic emulsion.

8. A method for preparing the lightweight self-waterproof homogeneous thermal insulation wallboard according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Mixing: Mix a water reducing agent, an early strength agent, a cement reinforcing agent and water and stir them evenly to obtain a preparatory liquid, then add silicate cement, sulphoaluminate cement and reinforcing fiber into the preparatory liquid, stir evenly, then add lightweight aggregate, stir evenly, finally add steam-free powder, stir all the raw materials evenly to obtain cement slurry; S2, mold table vibration molding; S3. Natural curing: After standing at a temperature of 20-22°C for 2.8-3 hours, demould to obtain the board to be cured, place it in a dark and ventilated place for curing for 7.8-8 hours to obtain a lightweight self-waterproof homogeneous thermal insulation wallboard.

9. The method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard according to claim 8, characterized in that: In the step S1, silicate cement, sulphoaluminate cement and reinforcing fiber are firstly mixed evenly and then blended with the preparatory liquid.

10. The method for preparing a lightweight self-waterproof homogeneous thermal insulation wallboard according to claim 8, characterized in that: In the step S1, acrylic emulsion is added and mixed with a water reducing agent, an early strength agent, a cement reinforcing agent and water to obtain a preparatory solution.